2022
DOI: 10.3390/ijerph19031868
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Sleep and Mental Health in Adolescents: Results from the UK Millennium Cohort Study

Abstract: (1) Background: There is a growing interest in investigating the relationship between sleep and mental health development in adolescents. This study aims to further investigate this relationship by identifying the specific associations between several sleep problems in adolescents and several mental health areas, and the role of gender in these associations. (2) Methods: Data from the Millennium cohort survey containing 11,553 individuals at 13–14 years old was included. Nighttime sleep duration and bedtime du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This may be partly explained by the 18% difference in boys’ and girls’ externalising problems scores (boys > girls) which mirror SDQ norms for UK youth [ 70 ]. Furthermore, sleep efficiency is influenced by number of night awakenings (in our analysis, p = .06 and p = .05 for associations with overall mental health and externalising problems, respectively) which was recently shown to be more strongly associated with externalising problems in English boys compared to girls in the nationally-representative Millennium Cohort Study [ 71 ]. These results emphasise the potential importance of sleep quality for boys reducing the risk of hyperactivity and conduct problems.…”
Section: Discussionmentioning
confidence: 79%
“…This may be partly explained by the 18% difference in boys’ and girls’ externalising problems scores (boys > girls) which mirror SDQ norms for UK youth [ 70 ]. Furthermore, sleep efficiency is influenced by number of night awakenings (in our analysis, p = .06 and p = .05 for associations with overall mental health and externalising problems, respectively) which was recently shown to be more strongly associated with externalising problems in English boys compared to girls in the nationally-representative Millennium Cohort Study [ 71 ]. These results emphasise the potential importance of sleep quality for boys reducing the risk of hyperactivity and conduct problems.…”
Section: Discussionmentioning
confidence: 79%
“…The relationship between mood and sleep is complex and bidirectional because poor mood and anxiety can worsen insomnia and vice versa. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the PDS profile presented the lowest scores for all mental health scubscales. While sleep has not been as well investigated as physical activity and sedentary behavior (e.g., screen time) in children and adolescents (Wilhite et al, 2023), the extant research on sleep clearly demonstrates the critical importance of sleep quality and sleep duration to mental health, especially during late childhood and adolescence (e.g., Coulombe et al, 2011;McMakin & Alfano, 2015;Qiu & Morales-Muñoz, 2022). In a survey study of 4250 youth ages 5-17, Bang et al (2020) found that sleep duration was a particularly important correlate of psychosocial health compared to physical activity and screen time and the authors considered the finding to be clinically meaningful.…”
Section: Research Questionmentioning
confidence: 99%